2015
DOI: 10.1016/j.ajhg.2015.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Symmetrical Dose-Dependent DNA-Methylation Profiles in Children with Deletion or Duplication of 7q11.23

Abstract: Epigenetic dysfunction has been implicated in a growing list of disorders that include cancer, neurodevelopmental disorders, and neurodegeneration. Williams syndrome (WS) and 7q11.23 duplication syndrome (Dup7) are rare neurodevelopmental disorders with broad phenotypic spectra caused by deletion and duplication, respectively, of a 1.5-Mb region that includes several genes with a role in epigenetic regulation. We have identified striking differences in DNA methylation across the genome between blood cells from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
41
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 80 publications
(67 reference statements)
0
41
0
Order By: Relevance
“…Because 7q11.23 band harbours different DNA methylation‐controlling genes (like GTF2I and GTF2IRD1 ), it can be speculated that the overexpression of one or more genes of this region causes the methylation‐dependent under‐regulation of other genes involved in brain tissue development (Strong et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…Because 7q11.23 band harbours different DNA methylation‐controlling genes (like GTF2I and GTF2IRD1 ), it can be speculated that the overexpression of one or more genes of this region causes the methylation‐dependent under‐regulation of other genes involved in brain tissue development (Strong et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…It has also been reported that disruption of epigenetic regulation is involved in many psychiatric disorders (Geaghan & Cairns, ). Although the epigenetic mechanisms underlying WS are not yet clearly understood, a recent study showed that aberrant DNA methylation occurs not only in the 7q11.23 region but also throughout the genomes of WS patients (Strong et al., ). Thus, epigenetic dysregulation may play a significant role in the upregulation of the three WS‐associated modules (M4, M11, and M12) in this study.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15] The International Consortium on Brain and Behavior in 22q11.2DS has collectively described the prevalence of psychiatric diagnoses in different age groups based on 15 clinical cohorts, reporting a change in prevalence of mental disorders in 22q11.2DS individuals throughout the lifespan. 1 In these clinically ascertained cohorts, one-third of carriers have a below-average intellectual level (IQ, [70][71][72][73][74][75][76][77][78][79][80][81][82][83][84] with adults frequently diagnosed with more severe levels of impairment. [16][17][18] ADHD, particularly the inattentive type, is~10 times more prevalent in children with the deletion, 19 with prevalence estimates ranging from 15.6 to 37% across different studies.…”
Section: Introductionmentioning
confidence: 99%